2015
DOI: 10.1016/j.jht.2015.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Clinical assessment of the infant and child following perinatal brachial plexus injury

Abstract: STUDY DESIGN Literature review INTRODUCTION After perinatal brachial plexus injury (PBPI), clinicians play an important role in injury classification as well as the assessment of recovery and secondary conditions. Early assessment guides the initial plan of care and influences follow-up and long-term outcome. PURPOSE To review methods used to assess, classify and monitor the extent and influence of PBPI with an emphasis on guidelines for clinicians. METHODS We use The International Classification of Func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 93 publications
0
15
1
1
Order By: Relevance
“…allied health care or psychosocial) and, if insufficient, interdisciplinary rehabilitation care is provided (Ramos and Zell, 2000; Smania et al, 2012). A considerable proportion of patients are discharged from clinical follow-up at the Leiden Nerve Center, either in their first year of life because of spontaneous recovery without indications for any interventions or later on in their care trajectory if good functional recovery takes place after conservative or surgical treatment (Bain et al, 2009; Bialocerkowski et al, 2005; Bialocerkowski and Gelding, 2006; Coroneos et al, 2015b; Duff and DeMatteo, 2015; Pondaag and Malessy, 2014; Socolovsky et al, 2015). Discharge from follow-up necessitates a low threshold for renewed consultation but also satisfactory information for both parents and patients.…”
Section: Introductionmentioning
confidence: 99%
“…allied health care or psychosocial) and, if insufficient, interdisciplinary rehabilitation care is provided (Ramos and Zell, 2000; Smania et al, 2012). A considerable proportion of patients are discharged from clinical follow-up at the Leiden Nerve Center, either in their first year of life because of spontaneous recovery without indications for any interventions or later on in their care trajectory if good functional recovery takes place after conservative or surgical treatment (Bain et al, 2009; Bialocerkowski et al, 2005; Bialocerkowski and Gelding, 2006; Coroneos et al, 2015b; Duff and DeMatteo, 2015; Pondaag and Malessy, 2014; Socolovsky et al, 2015). Discharge from follow-up necessitates a low threshold for renewed consultation but also satisfactory information for both parents and patients.…”
Section: Introductionmentioning
confidence: 99%
“…Different aspects of diverse outcome measured were discussed with the ICF as starting point; it was concluded that evaluation focus may shift during the life of an infant with BPBI 21. In the infant age, the assessment focus should be on impairment , which gradually shifts to activity at school age and to participation during adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…20 Duff and DeMatteo provide a narrative review that describes evaluation methods that can be useful in the evaluation of children with a BPBI. 21 The methods and outcomes of our Delphi surveys were reported in accordance to the standards set in a recent review. 22 International participants reached consensus on a number of items, which we depicted in a template for use in the clinic (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Despite several studies investigating body structure/function, there is minimal information on activity and participation levels of children with OBPP with different injury types (12)(13)(14). Therefore, the present study aims to investigate the activity and participation levels of preschool children with different types of OBPP.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to body structure dysfunctions, activity and participation restrictions are also common (11). However, three different reviews investigating clinical evaluations and outcome measures in OBPP reported that the studies merely focused on body structure/function and that more studies are needed to investigate the domains of activity, participation, environmental, and personal factors according to the International Classification of Functioning, Disability and Health (ICF) (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%